Jurusan Manajemen Fakultas Ekonomika dan Bisnis Universitas Diponegoro - Agusta, Sheila Rizkylia; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2014)
This research is titled “Analysis of the influence of Transformational Leadership, Compensation Satisfaction, and Organizational Commitment on Employee Performance